Master of souls : a mystery of ancient Ireland - Tremayne, Peter (Tremayne, Peter. Sister Fidelma novels., 2007)
Sister Fidelma and Brother Eadulf investigate the killing of Abbess Faife and the disappearances of six young women accompanying her on a pilgrimage, looking for a link between these crimes and the bludgeoning death of an aging abbey scholar.